Effects of Low-Level Blast Exposure on the Nervous System: Is There Really a Controversy? - Elder, Gregory A.; Stone, James R.; Ahlers, Stephen T. (Frontiers in Neurology, 2014)
High-pressure blast waves can cause extensive CNS injury in humans. However, in combat settings such as Iraq and Afghanistan, lower level exposures associated with mild TBI (mTBI) or subclinical exposure have been much more common. Yet controversy exists concerning what traits can be attributed to low-level blast, in large part due to the difficulty of distinguishing blast-related mTBI from post-traumatic stress disorder (PTSD). We describe how TBI is defined in humans and the problems posed in using current definitions to recognize blast-related mTBI. We next consider the problem of applying definitions of human mTBI to animal models, in particular that TBI severity in humans is defined in relation to alteration of consciousness at the time of injury, which typically cannot be assessed in animals. However, based on outcome assessments a condition of “low-level” blast exposure can be defined in animals that likely approximates human mTBI or subclinical exposure. We review blast injury modeling in animals noting that inconsistencies in experimental approach have contributed to uncertainty over the effects of low-level blast. Yet animal studies show that low-level blast pressure waves are transmitted to the brain. In brain low-level blast exposures cause behavioral, biochemical, pathological and physiological effects on the nervous system including the induction of PTSD-related behavioral traits in the absence of a psychological stressor. We review the relationship of blast exposure to chronic neurodegenerative diseases noting the paradoxical lowering of Abeta by blast, which along with other observations suggest that blast-related TBI is pathophysiologically distinct from non-blast TBI. Human neuroimaging studies show that blast-related mTBI is associated with a variety of chronic effects that are unlikely to be explained by co-morbid PTSD. We conclude that abundant evidence supports low-level blast as having long-term effects on the nervous system.